"Cumbia Fusión": Development and impact of an "Alternative" music scene in Lima - Olazo, Jorge (2023)
This article analyzes the development of the cumbia fusion (or «alternative» cumbia) scene in Lima, Peru, between 2010 and 2020. It demonstrates its impact in the change of programming criteria in big outdoor festivals, which only used to feature rock and pop bands, and now include not only this «alternative" cumbia bands, but also traditional cumbia orchestras and artists that were not accepted before. This analysis has been done primarily based on in-depth interviews with musicians and promoters of this scene, using the theoretical framework of Small (1998), Gell (1998), Straw (1991) and Bennet (2004). The career of two bands representative of this «alternative» scene, Olaya Sound System and La Nueva Invasión are used as case studies.